Home dialysis bulletin, a journal to support home dialysis - Christian Verger (RDPLF, 2021)
With issue 2 of volume 4, of this month, June 15, 2021, the Home Dialysis Bulletin (original journal title: Bulletin de la Dialyse à Domicile (BDD)) begins its fourth year of publication. Over the past three years, it has gradually become a benchmark medium for clinical research in the field of home dialysis for both nursing staff and nephrologists. It is referenced in Sherpa/Romeo [1], and each article has a CrossRef identifier. All articles benefit from perpetual archiving and have obtained the SEAL quality logo for open access journals from the referencer DOAJ [2]. The abstracts of articles have been viewed 33,840 times, and the French versions of articles have been downloaded in pdf format 19,164 times. It is widely read by caregivers and nephrologists regardless of the mode of exercise, as our recent survey revealed [3]. But dissemination outside the French-speaking world has also been growing steadily thanks to systematic bilingual publication, and 2,640 English versions of articles have been downloaded. Our privileged relations with the International Society for Peritoneal Dialysis (ISPD) [4] have enabled the translation and dissemination into French of international guidelines, when authorized.. The Bulletin de la Dialyse à Domicile appears to be one of the best supports for the development of home dialysis in France and Francophonie while maintaining close links with the English-speaking community. This success was made possible thanks to the work of the authors, whom we would like to thank for their support. Thanks also to the members of our editorial board. We also warmly thank our reviewers, who carry out the critical analysis of the published articles, usually within very short deadlines: Aguilera Didier (France), Azar Raymond (France), Bammens Bert (Belgium), Bataille Stanislas (France), Beaudreuil Séverine (France), Beaume Julie (France), Béchade Clémence (France), Ben Abdallah Taieb (Tunisia), Benamar Loubna (Morocco), Cassagne Brigitte (Switzerland), Caudwell Valérie (France), Chaffara Emmanuel (France), Chanliau Jacques (France), Collart Fredéric (Belgium), Courivaud Cécile (France), de Arteaga Javier (Argentina), Descot Lisa (France), Desitter Arielle (France), Divino José (USA), Durand Pierre-Yves (France), El Esper Najeh (France), Fabre Emmanuel (France), Faller Bernadette (France), Fessi Hafedh (France), Fibach Eitan (Israel), Francois Karlien (Belgium), Goffin Eric (Belgium), Grillon Antoine (France), Guillouet Sonia (France), Jager Rachel (France), Kieron Donovan (UK), Landru Isabelle (Fran ce), Lanot Antoine (France), Laruelle Eric (France), Mougel Sophie (France), Thierry Lobbedez (France), Laville Maurice (France), Morel Bertrand (France), Morelle Johann (Belgium), Mougel Sophie (France) , Nortier Joelle (Belgium), Padernoz Marie (France), Petitclerc Thierry (France), Pourcine Franck (France), Pouteau Lise-Marie (France), Poux Jean-Michel (France), Pujo Myriam (France), Querin Serge ( Belgium), Rodrigues Anabela (Portugal), Rostoker Guy (France), Rousseau-Gagnon Mathieu (Canada), Sanchez Emilio (Spain), Seret Guilaume (France), Simon Pierre (France), Sqalli Tarik (Morocco), Stéphanie Gentile ( France), Target Natalia (France), Testa Angelo (France), Touré Fatouma (France), Treille Serge (France), Urena Pablo (France), Van Biesen Wim (Belgium), Veniez Ghislaine (France), Vernier Isabelle ( France), Landi Vincent (France), Vrtovsnik François (France). More diffusion and improvement will only be possible if we continue to receive high-quality articles, and we hope that non-academics and academics, nurses and doctors will help us achieve this goal in the interest of all and of home dialysis ; so that these physicians and nurses teams will have easily accessible documentation at their disposal to enable them to exchange their knowledge in the service of patients, while sharing in both english and french language. 1 - https://v2.sherpa.ac.uk/id/publication/39007 2 - https://doaj.org/apply/seal/ 3 - Verger Christian, Max Dratwa, Pierre-Yves Durand, Jacques Chanliau, Eric Goffin, Thierry Petitclerc, Belkacem Issad, Ghislaine Veniez, Isabelle Vernier, Fatouma Toure, and Cécile Courivaud. 2020. «Assessment of the Interest of a French Language Journal Specializing in Home Dialysis». Bull Dial Domic 3 (4), 227-39. https://doi.org/10.25796/bdd.v3i4.58833. 4 - https://ispd.org/